Frederick Law Olmsted - Olmsted, Frederick Law, 1822-1903; Hubbard, Theodora Kimball, 1887-1935; Olmsted, Frederick Law, 1870-1957 (Salt Lake City, UT : Project Gutenberg, 2023)
"Frederick Law Olmsted: Landscape Architect, Vol. 1, Early Years and Experiences" is a historical account published in the early 20th century. This volume presents the professional papers of Frederick Law Olmsted, a seminal figure in landscape architecture, showcasing his early years and experiences that shaped his esteemed career. The book covers the foundational aspects of Olmsted's professional journey, including personal insights, biographical notes, and significant influences that catalyzed his approach to landscape design. The opening portion introduces readers to the diverse range of Olmsted's writings and the context in which they were created. It highlights the importance he placed on documenting his professional dealings, emphasizing his desire to present landscape architecture to the public in a favorable light. Furthermore, it touches upon his interactions with prominent figures, like Calvert Vaux, and his earnest engagement in various projects, such as designing Central Park. Overall, the beginning of the book sets the stage for an exploration of Olmsted's thoughts, methodologies, and the rich legacy he left in landscape architecture. (This is an automatically generated summary.)
Release date is 2023-05-15
The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Autobiographies; Olmsted, Frederick Law, 1822-1903; Landscape architects -- United States -- Biography